Molecular imaging and radionuclide therapy of pheochromocytoma and paraganglioma in the era of genomic characterization of disease subgroups - Taïeb, David (Endocr Relat Cancer, 2019)
In recent years, advancement in genetics has profoundly helped to gain a more comprehensive molecular, pathogenic, and prognostic picture of pheochromocytomas and paragangliomas (PPGLs). Newly discovered molecular targets, particularly that targets cell membranes or signaling pathways have helped move nuclear medicine in the forefront of PPGL precision medicine. This is mainly based on the introduction and increasing experience of various PET radiopharmaceuticals across PPGL genotypes quickly followed by implementation of novel radiotherapies and revised imaging algorithms. Particularly, (68)Ga-labeled-SSAs have shown excellent results in the diagnosis and staging of PPGLs and in selecting patients for PRRT as a potential alternative to (123/131)I-MIBG theranostics. PRRT using (90)Y/(177)Lu-DOTA-SSAs has shown promise for treatment of PPGLs with improvement of clinical symptoms and/or disease control. However, more well-designed prospective studies are required to confirm these findings, in order to fully exploit PRRT’s antitumoral properties to obtain the final FDA approval. Such an approval has recently been obtained for high‐specific-activity (131)I-MIBG for inoperable/metastatic PPGL. The increasing experience and encouraging preliminary results of these radiotherapeutic approaches in PPGLs now raises an important question of how to further integrate them into PPGL management (e.g. monotherapy or in combination with other systemic therapies), carefully taking into account the PPGLs locations, genotypes, and growth rate. Thus, targeted radionuclide therapy (TRT) should preferably be performed at specialized centers with an experienced interdisciplinary team. The future perspectives include the introduction of dosimetry and biomarkers for therapeutic responses for more individualized treatment plans, α-emitting isotopes, combination of TRT with other systemic therapies.